Deciphering interactions between the gut microbiota and the immune system via microbial cultivation and minimal microbiomes. Issue 1 (September 2017) - Clavel, Thomas; Gomes‐Neto, João Carlos; Lagkouvardos, Ilias; Ramer‐Tait, Amanda E.
Summary: The community of microorganisms in the mammalian gastrointestinal tract, referred to as the gut microbiota, influences host physiology and immunity. The last decade of microbiome research has provided significant advancements for the field and highlighted the importance of gut microbes to states of both health and disease. Novel molecular techniques have unraveled the tremendous diversity of intestinal symbionts that potentially influence the host, many proof‐of‐concept studies have demonstrated causative roles of gut microbial communities in various pathologies, and microbiome‐based approaches are beginning to be implemented in the clinic for diagnostic purposes or for personalized treatments. However, several challenges for the field remain: purely descriptive reports outnumbering mechanistic studies and slow translation of experimental results obtained in animal models into the clinics. Moreover, there is a dearth of knowledge regarding how gut microbes, including novel species that have yet to be identified, impact host immune responses. The sheer complexity of the gut microbial ecosystem makes it difficult, in part, to fully understand the microbiota‐host networks that regulate immunity. In the present manuscript, we review key findings on the interactions between gut microbiota members and the immune system. Because culturing microbes allows performing functional studies, we have emphasized the impact of specific taxa or communities thereof. We also highlight underlying molecular mechanisms and discuss opportunities to implement minimal microbiome‐based strategies.